2021
DOI: 10.1371/journal.pntd.0009237
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics reveals mechanisms that underlie insecticide resistance in Culex pipiens pallens Coquillett

Abstract: Mosquito control based on chemical insecticides is considered as an important element of the current global strategies for the control of mosquito-borne diseases. Unfortunately, the development of insecticide resistance of important vector mosquito species jeopardizes the effectiveness of insecticide-based mosquito control. In contrast to target site resistance, other mechanisms are far from being fully understood. Global protein profiles among cypermethrin-resistant, propoxur-resistant, dimethyl-dichloro-viny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 116 publications
1
15
0
Order By: Relevance
“…pipiens pallens . Furthermore, Zhang et al [ 37 ] revealed the differentially expressed proteins in insecticide resistance Cx . pipiens pallens coquillett in Shandong Province, China, similar to differentially expressed proteins found in our study, i.e., cytochromes-related, motor-related, ribosomal, GST, cuticle, and HSPs ( S1 File ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pipiens pallens . Furthermore, Zhang et al [ 37 ] revealed the differentially expressed proteins in insecticide resistance Cx . pipiens pallens coquillett in Shandong Province, China, similar to differentially expressed proteins found in our study, i.e., cytochromes-related, motor-related, ribosomal, GST, cuticle, and HSPs ( S1 File ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cuticle proteins and their assembly pattern influenced the integrity of the cuticle [ 37 , 51 ]. This study identified several insect cuticle proteins differentially expressed in ANOVA and t-test analyses, including pupal cuticle protein, putative (A0A1S4FZ80), cuticle protein 2 (Q17LN8), cuticle protein 5 (Q16I56) in the permethrin and temephos resistant adults and larvae Ae .…”
Section: Discussionmentioning
confidence: 99%
“…To observe changes at the RNA level, molecular techniques such as real-time polymerase chain reaction (RT-PCR), differential display reverse transcription PCR, northern blot and microarrays may be used. For protein estimation enzyme assays, various techniques such as enzyme linked enzyme-linked immunosorbent assay (ELISA), western blot, sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), and matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF) may be used [65,66]. In addition to this, to study the mechanism of resistance at the molecular level through proteomics, the identification of resistance-related proteins with their expression profiling can provide knowledge of the activity of proteins related to insecticide resistance in insects [67].…”
Section: Methods Of Detection Of Insecticide Resistancementioning
confidence: 99%
“…quinquefasciatus from Zanzibar was determined [86]. These assays provided evidence for insecticide resistance caused due to target site mutations and metabolic alterations at the genetic level [87].…”
Section: Genotypic Assaysmentioning
confidence: 99%
“…Isobaric tags for relative and absolute quantification (iTRAQ), as a highly advanced proteomic platform, can identify differentially regulated proteins more accurately and provide reliable quantitative information. This method labels protein samples with unique isotopes to enable robust comparisons of different samples in a mixture and to study changes in protein levels under different experimental conditions ( De Mandal et al, 2020 ; Zhang et al, 2021 ). iTRAQ has been applied successfully to screen differentially expressed proteins (DEPs) after pathogen infection in mosquitos to understand host immune defense mechanisms ( Baldridge et al, 2017 ; Xin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%